COLORECTAL CANCER - Kholliyeva Shakhlo Bakhtiyorovna; Hamzayeva Nargiza Rajabboyevna (Journals Park Publishing, 2022)
Colorectal cancer (CRC) is the second most diagnosed disease in the world. It is the fourth leading cause of cancer-related death. The high probability of developing CRC is related to western lifestyle, age, and personal history of chronic disease. CRC development is a multi-stage process that involves a sequence of genetic, histological, and morphological changes that accumulate over time. In addition, depending on the origin of the mutations, CRC can be classified as familial, sporadic, and hereditary, based on which a therapeutic plan is developed for the CRC patient.
Keywords: cancer; mutation; screening